2019
DOI: 10.12944/crnfsj.7.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Antioxidant and Antidiabetic Potency of Melinjo (Gnetum Gnemon) Seed Protein Hydrolysate at Different Stages of Seed Maturation

Abstract: roteins hydrolyzed from melinjo seeds (Gnetum gnemon) at green (GM), yellow (YM) and red (RM) stages of maturity were studied for their effectiveness in antioxidant and antidiabetic activities. The seed protein extract was hydrolyzed using alcalase 2.4L, and the resulting hydrolysates with the highest degree of hydrolysis, protein profile, and the most potent contributors to antioxidant and invitro antidiabetic activities were identified. The degree of hydrolysis value of hydrolysates ranged from 52-84%, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
(40 reference statements)
0
13
0
1
Order By: Relevance
“…One interesting work reports that the Alcalase hydrolysis of melinjo seeds (Gnetum gnemon) at different stages of maturity (green, yellow and red) generated hydrolysates with different antioxidant activities [215]. Another study shows that the Alcalase hydrolysis of J o u r n a l P r e -p r o o f defatted garden cress (Lepidium sativum) seed meal protein improved their antioxidant activity [216].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…One interesting work reports that the Alcalase hydrolysis of melinjo seeds (Gnetum gnemon) at different stages of maturity (green, yellow and red) generated hydrolysates with different antioxidant activities [215]. Another study shows that the Alcalase hydrolysis of J o u r n a l P r e -p r o o f defatted garden cress (Lepidium sativum) seed meal protein improved their antioxidant activity [216].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The G. gnemon has invitro antidiabetic and showed α-amylase and α-glucosidase inhibitory activity. The hydrolyzate of green seeds was found to be more effective than yellow seeds and red of old seeds with red color (Supriyadi, Arum, Nugraha, Ratnadewi & Siswoyo, 2019 Nurhartadi., 2015), so it is the potential to be used as a natural preservative. Parhusip & Sitanggang (2011) reported that seed extract G. genimon inhibits bacterial growth of Aspergillus flavus, Bacillus careus, Staphylococcus aureus, and Enterobacter aerogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Gnetum gnemon known as melinjo tree is a very popular vegetable ingredient and can be found in various regions in Indonesia. The indigenous people of Indonesia use melinjo as vegetables or processed delicacies (Supriyadi et al 2019). Beside its seed can be processed as chip, almost all parts can be consumed.…”
Section: The Highest Conservation Valuementioning
confidence: 99%